Rheology in polymer processing : modeling and simulation - Wilczynski, Krzysztof (Hanser Publishers, 2021)
Rheology in Polymer Processing introduces the fundamentals of rheology and rheometry as the basis for modeling and computer-aided design of plastics processing. The logically structured content enables the reader to intelligently use the tools of computer-aided design and modeling of plastics processing, with correct interpretation of the results.